Republic of Madagascar : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper presents a Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report for Madagascar. The assessment reveals that following a strong noninflation growth performance in 2003, macroeconomic developments in 2004 have been affected by adverse exogenous shocks. Madagascar is making good progress in implementing its poverty reduction strategy, which is delivering results. Primary net enrolment rates have increased from about 70 percent in 2002 to 84 percent in 2003/04. The roads program has been successful and rehabilitated about 1,850 km of roads, a threefold increase over 2001.